2014
DOI: 10.3390/nu6093847
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Vitamin D3 Supplementation Does Not Prevent Colonic Inflammation or Modulate Bone Health in IL-10 Knockout Mice at Young Adulthood

Abstract: Inflammatory bowel disease (IBD) is an idiopathic disease that can impair bone metabolism. Low vitamin D status has been implicated in its progress. This study used interleukin (IL)-10 knockout (KO) mice, that develop an intestinal inflammation when housed in a non-sterile environment, to determine if supplementation with vitamin D3 throughout life could mitigate inflammation and attenuate the lower bone mineral content (BMC) and density (BMD), and bone strength. Female IL-10 KO mice were randomized 25 or 5000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…39 Transgenic expression of human VDR in the mouse epithelium ameliorates IL-10 knockout colitis, 38 whereas 1,25(OH) 2 D 3 treatment does not. 40 VDR expression reduces epithelial pro-inflammatory cytokine production and immune cell infiltration into the mucosa, 38 indicating that epithelial VDR signaling is critical in modulating the immune response in IBD. Thus, VDR could be both a cause (e.g.…”
Section: Relevance Of Intestinal Vdr In Ibdmentioning
confidence: 99%
“…39 Transgenic expression of human VDR in the mouse epithelium ameliorates IL-10 knockout colitis, 38 whereas 1,25(OH) 2 D 3 treatment does not. 40 VDR expression reduces epithelial pro-inflammatory cytokine production and immune cell infiltration into the mucosa, 38 indicating that epithelial VDR signaling is critical in modulating the immune response in IBD. Thus, VDR could be both a cause (e.g.…”
Section: Relevance Of Intestinal Vdr In Ibdmentioning
confidence: 99%
“…Findings from our group have demonstrated that normal bone development, measured as BMD and biomechanical bone strength, occurs with a significantly lower level of vit D (25 IU/kg) in mice fed an obesogenic diet, in inflammatory prone female mice or in healthy male mice ( Glenn et al, 2014 ; Villa et al, 2016 ; Jahani et al, 2014 ). In these studies, dietary Ca was kept constant at 5 g/kg and diets were fed from weaning until 3 ( Glenn et al, 2014 ; Jahani et al, 2014 ) or 7 months of age ( Villa et al, 2016 ). In growing female Sprague-Dawley rats, Ca levels were manipulated by examining both lower and higher levels than in the AIN-93G reference diet, 1 through 7 g/kg.…”
Section: Introductionmentioning
confidence: 96%
“…We have previously demonstrated that there is a window of opportunity during early life for novel food components, such as soy isoflavones, to favourably program bone outcomes at early adulthood in terms of higher BMD and improved bone structure and bone strength in female mice ( Kaludjerovic and Ward, 2010 ; Dinsdale et al, 2012 ; Kaludjerovic and Ward, 2009 ; Kaludjerovic and Ward, 2015 ). While these studies have used the AIN-93G reference diet that is recommended for supporting growth, pregnancy and lactation, the levels of vitamin D (vit D, 1000 IU/kg) and calcium (Ca, 5 g/kg) in this diet may be higher than required for normal bone development, measured as BMD and bone structure in mice and rats ( Glenn et al, 2014 ; Villa et al, 2016 ; Hunt et al, 2008 ). Findings from our group have demonstrated that normal bone development, measured as BMD and biomechanical bone strength, occurs with a significantly lower level of vit D (25 IU/kg) in mice fed an obesogenic diet, in inflammatory prone female mice or in healthy male mice ( Glenn et al, 2014 ; Villa et al, 2016 ; Jahani et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the murine TNBS-model of colitis, vitamin D deficiency lead to worse disease activity and fibrosis as determined by collagen deposition, possibly through the TGF-β1/Smad3 pathway [ 38 ]. Similarly, in the IL-10 −/− model of colitis, vitamin D deficiency exacerbated disease while supplementation ameliorated disease [ 39 , 40 ], which correlates well with the aforementioned inverse relations between IL-10 and vitamin D seen in CD patients [ 35 ]; however, vitamin D supplementation did not reduce colonic inflammation in this model [ 41 ]. Double IL-10/VDR knockout studies demonstrated that loss of vitamin D resulted in decreased lymphocyte function leading to increased intestinal inflammation in the absence of IL-10 [ 42 ].…”
Section: Inflammatory Bowel Diseasementioning
confidence: 65%